Kupffer cells depletion alters cytokine expression and delays liver regeneration after Radio-frequency-assisted Liver Partition with Portal Vein Ligation. (April 2022) - Zhang, Weikang; Zhu, Xiwen; Tang, Yong; Li, Jinzheng; Miao, Chunmu; Gong, Jianping; Li, Peizhi
Abstract: Radio-frequency-assisted Liver Partition with Portal Vein Ligation (RALPP) induces comparable hypertrophy of the liver remnant compared to Associating Liver Partition and Portal vein ligation for Staged hepatectomy (ALPPS) in humans. However, whether it is significantly improved compared to ALPPS is unclear, and the underlying mechanisms of liver regeneration after RALPP need to further investigate. The present study was to develop an animal model mimicking RALPP and explore mechanisms of liver regeneration. The mice in RALPP group received liver radiofrequency ablation and 90% portal vein ligation (PVL), followed by resection of the targeted liver within two days after the first surgery. The mice in ALPPS group underwent 90% PVL combined with parenchyma transection. Controls received liver radiofrequency ablation (RAF group) or PVL (PVL group) or small left lateral lobe (LLL group) resection alone. Liver regeneration was assessed by liver weight and proliferation-associated molecules. The role of Kupffer cells (KCs) in liver regeneration was investigated after RALPP. The results showed that RALPP induced comparable liver regeneration compared to ALPPS, but with less liver injury and mortality in mice. RALPP led to over-expression of TNF-α and IL-6 in the circulating plasma compared with PVL. KCs infiltrating in liver tissues was a characteristic of mice in the RALPP group. KCs depletion markedly depressed cytokine expression and delayed liver regeneration after RALPP. These results suggested that RALPP in mice induced accelerated liver regeneration similar to ALPPS, but safer than ALPPS. KCs depletion altered cytokine expression and delayed liver regeneration after RALPP. Highlights: RALPP induced comparative liver regeneration but less liver injury compared to ALPPS after step I. RALPP resulted in significant hypertrophy of the liver remnant with less mortality compared with ALPPS after step II. Kupffer cells depletion alters cytokine expression and delays liver regeneration after RALPP.